Research on Super-resolution Location Technology of Leakage Source Based on Ultrasonic Array Sensor. Issue 1 (1st March 2022) - Bian, Xu; Tian, Biwan; Jin, Shijiu
Abstract: Leakage in the pressure structure is a problem that must be paid attention to, especially in some special applications, such as spacecraft, which will have a serious impact on the entire system. This paper presents a new method of leak source location based on a single sensor array. The elastic wave excited by the leakage is collected by an array sensor placed on the wall, and then the frequency-space characteristics of these signals are analyzed to obtain the spatial point that meets these characteristics, that is, the spatial location of the leakage source. At the same time, combining the super-resolution technology and the randomness of the signal, integrating the distribution maps of the positioning results in different time periods, and finally obtaining a high-precision estimation of the location of the leakage source. The experimental results show that, under the conditions considered in this paper, the average value of the absolute positioning error on a square meter board is about 2 cm.